Organocatalytic Synthesis of Benzimidazole Derivatives - Lafuente, Leticia; Maidana, Lautaro G.; Bisceglia, Juan A.; Iribarren, Adolfo M.; Lewkowicz, Elizabeth S. (Synthesis, 2022)
A synthetic route for the production of chiral derivatives of benzimidazole is presented. Different commercially available amines are evaluated as organocatalysts for the stereoselective aldol addition of N1-benzimidazolyl acetaldehyde, previously prepared by N-alkylation of benzimidazole, with cyclic ketones. When cyclohexanone was used, l-prolinamide proved to be the most efficient catalyst, giving (S)-2-((R)-2-(1H-benzo[d]imidazol-1-yl)-1-hydroxyethyl)cyclohexanone in 92% yield, 90% ee and 92:8 dr (anti/syn).
Keywords: benzimidazole; chiral; organocatalysis; l-prolinamide; imidazolidinone